2010
DOI: 10.1021/cn100042d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Novel Chalcone Derivatives with 99mTc/Re Complexes as Potential Probes for Detection of β-Amyloid Plaques

Abstract: Four 99mTc-labeled chalcone derivatives and their corresponding rhenium analogues were tested as potential probes for imaging β-amyloid plaques. The chalcones showed higher affinity for Aβ(1-42) aggregates than did 99m Tc complexes. In sections of brain tissue from an animal model of AD, the four Re chalcones intensely stained β-amyloid plaques. In biodistribution experiments using normal mice,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 25 publications
2
70
0
Order By: Relevance
“…The tributyltin derivative 5 was prepared from the corresponding iodo derivative 4 using a iodo-totributyltin exchange reaction catalyzed by Pd(0) for a yield of 48%. The starting material 6 for the synthesis of the allyoxylated chalcone derivative 8 was prepared as previously reported 20 .…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The tributyltin derivative 5 was prepared from the corresponding iodo derivative 4 using a iodo-totributyltin exchange reaction catalyzed by Pd(0) for a yield of 48%. The starting material 6 for the synthesis of the allyoxylated chalcone derivative 8 was prepared as previously reported 20 .…”
Section: Chemistrymentioning
confidence: 99%
“…We have previously reported Aβ imaging agents based on flavonoid derivatives, such as flavones 15,16 , chalcones [17][18][19][20] , aurones 21,22 , and styrylchromones 23 studies demonstrated that chalcone derivatives fluoro-pegylated at the p-position of the 1-phenyl ring showed a sufficient brain uptake with a good binding capacity to Aβ plaques 19 . In addition, radioiodinated flavonoids, such as flavone and aurone derivatives, with a methoxy or oligoethyleneoxy group at the p-position of the 3-phenyl ring have the properties of high brain uptake and rapid clearance from the brain without significant decrease in the binding affinity for Aβ 15,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Initially, we designed and synthesized four 99m Tc-labeled Ono et al 5/38 chalcone derivatives with monoamine-monoamide dithiol (MAMA) and bis-amino-bis-thiol (BAT) (Figure 1) 29 . MAMA and BAT were selected as a chelation ligand taking into consideration the permeability of the blood-brain barrier, because they form an electrically neutral complex with 99m Tc 30 .…”
mentioning
confidence: 99%
“…MAMA and BAT were selected as a chelation ligand taking into consideration the permeability of the blood-brain barrier, because they form an electrically neutral complex with 99m Tc 30 . 99m Tc-BAT-chalcone (n=3) (Figure 1) showed good uptake into and rapid clearance from the brain in addition to high affinity for β-amyloid plaques, indicating it may be a promising probe for the detection of β-amyloid plaques in the brain 29 . Based on the positive results, we decided to further develop new 99m Tc imaging agents based on the flavonoid scaffold.…”
mentioning
confidence: 99%
See 1 more Smart Citation